Pengaruh Budaya Organisasi dan Kompensasi Karyawan Terhadap Kinerja Karyawan pada PT. Sumber Alfaria Trijaya, Tbk. di Makassar - Marsuki, Marsuki; Kapriani, Kapriani; Jusman, Ikhsan Amar (STIM-LPI Makassar, 2025)
The success of an organization or company is largely determined by employee performance. Every company will always strive to improve employee performance so that company goals can be achieved. One factor that can improve employee performance is organizational culture and compensation. The purpose of this study is to analyze the influence of organizational culture and compensation partially and simultaneously on employee performance at PT. Sumber Alfaria Trijaya, Tbk. in Makassar. This study uses a causal research type with a quantitative approach. The population in this study were 55 employees of PT. Sumber Alfaria Trijaya, Tbk. The sampling technique used was total sampling. Data collection was carried out by distributing questionnaires. The data analysis technique used was multiple linear regression analysis. The results of this study concluded that organizational culture and compensation had a significant effect partially and simultaneously on employee performance at PT. Sumber Alfaria Trijaya, Tbk. in Makassar.